Superior mesenteric artery blood flow in children with celiac disease - ERTEM ŞAHİNOĞLU, DENİZ (LIPPINCOTT WILLIAMS & WILKINS, 1998)
Background: Knowledge of splanchinic hemodynamics in celiac disease is scarce. The hemodynamic parameters of the superior mesenteric artery were evaluated by duplex Doppler ultrasonography in children with celiac disease to show whether histomorphologic changes in small bowel mucosa led to any alteration in splanchinic blood flow. Methods: The hemodynamic parameters of the superior mesenteric artery were evaluated by Doppler ultrasonography in 23 children with celiac disease. Ten patients were studied at the time of diagnosis. The remaining 13 children were studied after complete clinical and histologic recovery induced by gluten-free diet. Additionally, 9 patients out of 13 who were on a gluten-free diet for about 2 years were given gluten challenge, and superior mesenteric artery blood flow was measured after the challenge. The results were compared with those of healthy children. Results: Peak systolic velocity of the superior mesenteric artery was higher in untreated celiac patients than in healthy controls and treated celiac patients. Peak systolic velocity of the superior mesenteric artery in the treated group of children was close to that of control subjects, implying that successful treatment with gluten-free diet improves hemodynamic changes. The comparison of Doppler ultrasonographic measurements of the challenge group before and after the gluten challenge revealed that the peak systolic velocity, resistive index, and blood flow of the superior mesenteric artery were changed significantly. Conclusions: The pathophysiologic events in small bowel mucosa during the active phase of celiac disease induce same hemodynamic changes that can be detected noninvasively by duplex Doppler ultrasonography.
Keywords: celiac disease; child; Doppler ultrasonography; superior mesenteric artery blood flow; GLUTEN CHALLENGE; DOPPLER US; INFLAMMATION; ANTIGLIADIN; ANTIBODIES; FLOWMETRY; DIAGNOSIS; GLIADIN; MUCOSA; SPRUE